P468 Long-term function after transanal vs. transabdominal ileal pouch-anal anastomosis for ulcerative colitis: a multi-centre cohort study. (25th January 2019) - Chandrasinghe, P; Carvello, M; Wasmann, K; Tanis, P; Warusavitarne, J; Spinelli, A; Bemelman, W
Abstract: Background: The transanal approach has been introduced in ileal pouch-anal (IPAA) surgery to gain better exposure for the rectal dissection. It has been shown to be safe with lower morbidity than the trans-abdominal approach. The aim of this study was to compare functional outcome of transanal ileal pouch-anal anastomosis (ta-IPAA) with transabdominal (abd-IPAA) approach for ulcerative colitis (UC) using the Cleveland Global Quality of Life (CGQL). Methods: This is a multi-centre cohort of consecutive patients undergoing abd-IPAA or ta-IPAA for UC prospectively registered in the databases of three tertiary referral institutions between March 2002 to September 2017. Patient characteristics, surgical details and postoperative outcomes were retrieved. The primary end-point was pouch function determined by CGQL score. The questionnaire was administered to all patients with a functioning pouch for 12 months. Results: Ninety-nine patients with ta-IPAA were compared with 274 patients with abd-IPAA. A defunctioning stoma was created at the time of pouch construction in 46 (46%) patients undergoing ta-IPAA and in 130 (47%) patients with abd-IPAA ( p = 0.90). Thirty-day postoperative complications according to Clavien-Dindo classification ( p = 0.22) as well as anastomotic leak rates (13% vs. 6%), abd-IPAA and ta-IPAA, respectively, were comparable ( p = 0.09). Time to stoma closure did not differ between the two groups (abd-IPAA- 6 ± 7 vs. ta-IPAA- 5 ± 4 months; p = 0.72). Twelve months CGQL score was obtained for 251 patients in the abd-IPAA group and for 97 in ta-IPAA cohort. The CGQL index was comparable between the two groups (0.72 ± 0.15 vs. 0.75 ± 0.12; p = 0.07). Quality of health and energy level components were statistically higher for ta-IPAA (7.30 ± 1.53 vs. 7.73 ± 1.19, p = 0.01; 6.68 ± 1.74 vs. 7.17 ± 1.54, p = 0.01) while no difference was found for quality of life item (7.63 ± 1.52 vs. 7.62 ± 1.30, p = 0.73). Pouch failure (including defunction and excision) was reported in 40 of 298 (12%) patients undergoing abd-IPAA and in 1 patient (1%) having ta-IPAA during the follow-up period. Conclusions: ta-IPAA produces functional result comparable to transabdominal approach at 12 months after surgery.